Evaluación de Bacillus sp antárticos en la degradación de celulosa - Mera Loor, Antony Elian (2024)
The objective of the study was to evaluate the degradation of cellulose by applying strains (Bacillus sp) isolated in Antarctica. A unifactorial Completely Randomized Design (RCD) experimental design was used, which included five treatments (strains) and a control, with 24 experimental units for each of the three time periods, each lasting 72 hours. The isolated strains were grown on nutrient agar medium and subsequently incubated at 37°C for 24 hours in the absence of light. The evaluation of degradation was carried out by measuring the degradation zone in an enriched medium, at an ambient temperature of 37°C for 72 hours. The Congo red method was used to evaluate the degradation of carboxymethylcellulose. The data obtained were subjected to statistical analysis of variance (ANOVA) and the Tukey test was applied. The results showed that the T-29 strain maintained a cellulose degradation efficiency of 86.4%, followed by the GA-52 strain with a value of 81.9%, and the DEE-71 strain with 77.5%. On the other hand, treatments T-21 and T-13 showed degradation percentages of 75.5% and 57.1%, respectively. It was observed that strains T-29 and GA-52 showed a higher degradation rate when combined, compared to the other strains studied. In conclusion, these two strains demonstrated greater enzymatic degradation potential when used together, suggesting that they could have a synergistic effect on the cellulose degradation process.